HUBUNGAN LINGKUNGAN SOSIAL SEKOLAH DENGAN MINAT BELAJAR IPS DI MTS AL-MIZAN KECAMATAN SEKAYAM - Nur Fauzi Ihsan; Sri Buwono; Bambang Genjik S (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research aimed to find out how much is the relationship between the school social environment and the interest in learning Social Studies at MTs Al-Mizan in Sekayam. The research method used was quantitative descriptive research. The samples of this research were the seventh grade students and eighth grade students. The data were in the form of questionnaires about the school social environment with 3 indicators, namely the relationship between students and students, students and teachers, and students and the principal, while the questionnaires about interest in learning Social Studies consists of 4 indicators namely student interest, student involvement, student attention, and feeling happy. The results showed that the school social environment got the percentage of 65.35% categorized as quite well, while the interest in learning Social Studies got the percentage of 73.54% categorized as good. Based on the data analysis technique, it was found that the relationship between the school social environment and the interest in learning Social Studies was 0.571 with a predetermined standard of 0.05 at a significant level of 0.320. So, it showed that the result of tcount > ttable was 0.571 > 0.320. So, that the relationship of interest in reading with learning outcomes in the amount of 0.571 with quite strong criteria. Keywords: School Social Environment, Learning Interest, Social Studies (IPS).